KETERLIBATAN IBU DALAM LITERASI KELUARGA PADA PEMEBELAJARAN MENULIS PERMULAAN DI MASA PANDEMI COVID 1 - Wasi Widiastika; Prana Dwija Iswara; Rahman; Vismaia S. Damaianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Family is the first and foremost group of learning for children and plays an important role in children's education. By having a good family environment and being supported by good literacy activities, children certainly could be literate and have good cognitive, affective, and psychomotor competencies. In the current Covid-19 pandemic, the family, especially the mother's role as the main home manager, was very crucial in learning activities from home that are currently taking place. The purpose of the study described in this article was to analyze the mother's involvement in family literacy in early writing lessons during the Covid-19 pandemic. The method used was a survey method involving 6 mothers with higher education who decided to become full-time mothers who graduated from several wellknown universities in Indonesia. Data were collected through questionnaires and interviews. Data were analyzed descriptively quantitative. The results of data analysis indicated that a mother's involvement in family literacy could support the early writing skills of children who were still in low grade so that children could achieve indicators of early writing skills. The results of the study were required to be a reference for related groups regarding the direct involvement of mothers in the children learning process at home.